2018
DOI: 10.1159/000491019
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Natural Killer Cells in the Largest Diameter Lymph Nodes Is Associated with the Number of Retrieved Lymph Nodes and Lymph Node Size, and Is an Independent Prognostic Factor in Patients with Stage II Colon Cancer

Abstract: Objective: We previously reported that the largest diameter of retrieved lymph nodes (LNs) correlates with the number of LNs and is a prognostic factor in stage II colon cancer. We examine whether T, B, and natural killer (NK) cells in LNs are related to the number of LNs and survival. Methods: The subjects comprised 320 patients with stage II colon cancer. An LN with the largest diameter was selected in each patient. The positive area ratios of cells that stained for CD3 and CD20, and the numbers of CD56-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In a variety of preclinical models of hematological malignancies, STAT3 deficiency in NK cells improves tumor surveillance, recommending that STAT3 inhibitors could trigger the NK cells-induced cytotoxicity against leukemia ( 28 ). Moreover, a study in 320 patients with stage II colon cancer suggested that the density of NK cells is linked with the lymph nodes (LNs) frequencies and is an independent predictive factor ( 29 ). Similarly, a study in 180 gastric cancer patients verified a significant association between the NK cells percentage and overall survival of enrolled participants ( 30 ).…”
Section: Nk Cells In the Tumor Microenvironmentmentioning
confidence: 99%
“…In a variety of preclinical models of hematological malignancies, STAT3 deficiency in NK cells improves tumor surveillance, recommending that STAT3 inhibitors could trigger the NK cells-induced cytotoxicity against leukemia ( 28 ). Moreover, a study in 320 patients with stage II colon cancer suggested that the density of NK cells is linked with the lymph nodes (LNs) frequencies and is an independent predictive factor ( 29 ). Similarly, a study in 180 gastric cancer patients verified a significant association between the NK cells percentage and overall survival of enrolled participants ( 30 ).…”
Section: Nk Cells In the Tumor Microenvironmentmentioning
confidence: 99%
“…Bar et al [ 27 ] reported that lower percentages of NK cells resulted in a weaker immune response to residual leukemia and predicted a poor outcome in acute myeloid leukemia. The percentage of NK cells is an independent indicator for prognosis of colon cancer and is significantly correlated with the lymph nodes [ 28 ]. Yang et al [ 29 ] reported that patients with advanced pancreatic cancer possess NK cells of a unique subtype with anergic features; a high percentage of NKs predicts poor survival of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…High TIL levels occur in anti-tumor immune response and indicate a good prognosis in gastric cancer and breast cancer ( 18 , 19 ). Moreover, regulation of lymph node function by NK cells is associated with prognosis in patients with stage II colon cancer ( 20 ). Study have shown that the average fluorescence intensity of CD8 staining in peripheral blood of patients with grade 3 EEC is lower than that of healthy donors.…”
Section: Discussionmentioning
confidence: 99%